Risk factors for nosocomial infections after cardiac surgery in newborns with congenital heart disease - Heladia García; Beatriz Cervantes-Luna; Héctor González-Cabello; Guadalupe Miranda-Novales (Elsevier, 2018)
Background: Congenital heart diseases are among the most common congenital malformations. Approximately 50% of the patients with congenital heart disease undergo cardiac surgery. Nosocomial infections (NIs) are the main complications and an important cause of increased morbidity and mortality associated with congenital heart diseases. This study's objective was to identify the risk factors associated with the development of NIs after cardiac surgery in newborns with congenital heart disease. Methods: This was a nested case-control study that included 112 newborns, including 56 cases (with NI) and 56 controls (without NI). Variables analyzed included perinatal history, associated congenital malformations, Risk-Adjusted Congenital Heart Surgery (RACHS-1) score, perioperative and postoperative factors, transfusions, length of central venous catheter, nutritional support, and mechanical ventilation. Statistical analysis: Differences were calculated with the Mann-Whitney-U test, Pearson X2, or Fisher's exact test. A multivariate logistic regression was used to determine the independent risk factors. Results: Sepsis was the most common NI (37.5%), and the main causative microorganisms were gram-positive cocci. The independent risk factors associated with NI were non-cardiac congenital malformations (OR 6.1, CI 95% 1.3-29.4), central venous catheter indwelling time > 14 days (OR 3.7, CI 95% 1.3-11.0), duration of mechanical ventilation > 7 days (OR 6.6, CI 95% 2.1-20.1), and ≥5 transfusions of blood products (OR 3.1, CI 95% 1.3-8.5). Mortality attributed to NI was 17.8%. Conclusion: Newborns with non-cardiac congenital malformations and with >7 days of mechanical ventilation were at higher risk for a postoperative NI. Efforts must focus on preventable infections, especially in bloodstream catheter-related infections, which account for 20.5% of all NIs. Key Words: cardiac surgery, congenital heart disease, newborn, nosocomial infection